2015
DOI: 10.1016/j.triboint.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Cross hatched texture influence on the load carrying capacity of oil control rings

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…In specific, the friction reduction was up to 73%, as the ring-cylinder contact becomes more conformal. In this direction, significant part of this research about the oil control ring tribological behaviour is also reported by Biboulet et al 33 Their model includes the reaction of flat shape oil ring under cross-hatched textures cylinder liner solving the steady-state Reynolds equation. They concluded that cross-hatched cylinder liner substantially improves the hydrodynamic carrying capacity of the oil ring flat face, leading to thicker lubricant films which would reduce engine friction.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In specific, the friction reduction was up to 73%, as the ring-cylinder contact becomes more conformal. In this direction, significant part of this research about the oil control ring tribological behaviour is also reported by Biboulet et al 33 Their model includes the reaction of flat shape oil ring under cross-hatched textures cylinder liner solving the steady-state Reynolds equation. They concluded that cross-hatched cylinder liner substantially improves the hydrodynamic carrying capacity of the oil ring flat face, leading to thicker lubricant films which would reduce engine friction.…”
mentioning
confidence: 77%
“…Attempts to include the effects of textured cylinder liner in the compression ring tribological analysis have been made. The works of Tomanik et al, Checo et al and Biboulet et al showed the micro dimples effect on the cylinder liner and ring pack tribological performance respectively. Tomanik's study developed a one‐dimensional computer model in order to simulate surface topographies and to examine their effects on the flat and barrel faced ring combined with Greenwood and Trip contact model in the boundary lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Biboulet et al and Noutary et al proposed multi-grid techniques to solve deterministic hydrodynamic lubrication models with non-mass-conservative cavitation for the piston ring cylinder liner contact with measured textured surfaces. It was shown that the groove depth and density are important factors determining the load carrying capacity, whereas the groove shape has only a minor influence [137][138][139]. A deterministic mixed lubrication model was also proposed by Minet et al for mechanical seals applications.…”
Section: Full Deterministic Methodsmentioning
confidence: 99%
“…Zavos and Nikolakopoulos [20] presented a computational study regarding the effect of surface texturing on the tribological behavior of the piston ring. Tomanik et al [21], Biboutlet et al [22], and Urabe et al [23] studied the effects of various surface textures on the reduction in piston ring friction. It can be concluded that the efficiency of surface texturing on engine friction reduction has been recognized by a number of studies.…”
Section: Surface Modificationmentioning
confidence: 99%